Pemberdayaan Masyarakat Melalui Penanaman Jahe untuk Meningkatkan Kesejahteraan Masyarakat Pada GAPOKTAN di Desa Sangup Kecamatan Tamansari Kabupaten Boyolali - Tamara, Rinda Ocik (Islamic Management and Empowerment Journal, 2023)
This research aims to determine the process of community empowerment through planting ginger to improve community welfare in GAPOKTAN as well as the supporting and inhibiting factors in Sangup village, Tamansari District, Boyolali Regency using qualitative research. The results of this research explain that the empowerment process was carried out through a ginger planting program with the first stage, assessing regional potential; second, preparing activity plans; third, implementation of activity plans; fourth, monitoring until the expected activity results are achieved. The four empowerment processes were accompanied by LPTP Surakarta. The inhibiting factor is that community motivation is not strong enough so it requires the intervention of all elements.